Development of a Pseudo-Nine-Node Thick Plate Element. Issue 3 (3rd July 2022) - Cheng, Y.M.; Hu, B.; Wang, J.H.; Li, L.
Abstract: A highly accurate new quadrilateral thick plate element based on the Reissner–Mindlin theory is developed in this paper. The proposed element possesses nine nodes for improved accuracy, but the mid-sides and center nodes are condensed to form the element stiffness matrix so that it behaves as a four-node element externally, which is more convenient for practical engineering applications. The behavior of this new element, PLATE-Q9, is free from shear locking problems, and it can degenerate to the thin plate solution. The performance of this new plate element is compared with similar quadrilateral plate elements using static condensation under highly distorted mesh conditions. The numerical problems with some popular plate elements under adverse condition are highlighted, and some strange results are obtained. It is also demonstrated that the proposed quadrilateral element can still perform well under these special cases, and is able to pass through all the patch tests.